THE LONG - TERM EFFECTS OF UNTREATED CALCIUM DEFICIENCY IN CHILDREN, INCLUDING IT’S EFFECT ON BONE HEALTH AND OVERALL GROWTH - Ramesh Chaudhari, Vipra Dadheech, (EPRA International Journal of Research and Development (IJRD), 2023)
Calcium deficiency is a prevalent problem in children that can have long-term consequences for their bone health and overall development. Untreated calcium deficiency can have severe consequences, including frail and fragile bones, an increased risk of fractures and other bone injuries, and even rickets. Calcium is also necessary for numerous physiological processes, including muscle function, nerve transmission, and hormone secretion. Without sufficient calcium, these processes may be disrupted, resulting in a variety of health issues. This effect can be especially pronounced in adolescents experiencing rapid growth and development. Fortunately, parents and caregivers can take measures to prevent and treat calcium deficiency in children, including providing a balanced diet that includes calcium-rich foods and, in some cases, the use of supplements. By taking measures to prevent and treat calcium deficiency, we can ensure that children develop healthily and robustly.